Korean wave dan Generasi Z: Menjaga Pancasila di Era Globalisasi: Menjaga Pancasila di Era Globalisasi - Nisa, Qurrota Ainin (Maliki Interdisciplinary Journal, 2025)
In an era of complex globalization, Generation Z (Gen Z) is actively engaging with various global artistic and cultural expressions. One significant phenomenon is the Korean Wave (Hallyu), which includes Korean dramas, K-Pop music, and distinctive fashion trends. While the Korean Wave has the ability to shape national identity, research shows that its influence on Generation Z's sense of national identity is not significant. This reflects that although Gen Z is exposed to foreign cultures, they possess a distinctive approach to constructing their own identities. Generation Z is recognized as digital natives who leverage technology and social media to explore diverse forms of art and culture. They engage with worldwide content through platforms such as TikTok and Instagram, which enable them to share and create new trends. In this context, the Korean Wave serves not only as entertainment, but also as a tool to spread Pancasila values, such as tolerance and diversity, among this generation. Although Generation Z is influenced by foreign cultures, they still try to maintain their local identity. This indicates that Gen Z possesses the ability to assimilate elements from other cultures while also valuing their own cultural heritage. Therefore, the Korean Wave can be seen as a link between global culture and local values that are crucial to a nation's identity.